GEOMETRIC MORPHOMETRIC ANALYSIS OF SCAPULAR SHAPE AND MORPHOLOGICAL PHYLOGENY AMONG BARASINGHA, SLOTH BEAR, SMALL INDIAN CIVET, STRIPED HYENA, AND INDIAN PARIAH DOG (Applied Biological Research, 2025)
Understanding scapular morphology is essential for interpreting species-specific adaptations related to locomotion, muscle attachment, and ecological strategies. The present study employed geometric morphometric techniques to analyze scapular shape variation and morphological phylogeny in five mammalian species: barasingha (Rucervus duvaucelii), sloth bear (Melursus ursinus), small Indian civet (Viverricula indica), striped hyena (Hyaena hyaena), and Indian pariah dog (Canis lupus familiaris). The study aimed to determine how scapular morphology reflects species-specific functional adaptations. A total of 144 homologous landmarks were digitized from high-resolution images of the lateral and medial surfaces of the scapula. Shape variation was assessed using principal component analysis (PCA) and Procrustes analysis of variance (ANOVA). Morphology-based clustering was performed using hierarchical unweighted pair group method with arithmetic mean (UPGMA) dendrograms derived from PCA scores. Results indicated that the first principal component accounted for 80.40% of the total shape variance in species-wise analysis, primarily associated with variation in acromion process orientation and scapular spine morphology. Surface-wise PCA revealed a more balanced distribution of variance across components, with PC1, PC2, and PC3 explaining 33.71%, 20.81%, and 18.83% of the variance, respectively. Procrustes ANOVA demonstrated a significant effect of scapular surface on shape (F = 10.34, P < 0.0001), whereas size differences were not significant (P = 0.0888). The resulting phylogenetic dendrogram grouped the species into two major phenetic clusters. Overall, the study provides new insights into scapular shape diversity and its ecological and evolutionary implications among the examined mammalian taxa.
Keywords: Functional adaptation; geometric morphometrics; mammalian morphology; phylogeny; scapula